Profile of Students' Creative Thinking Skills in High School - Purwati, Selvira; alberida, Heffi (Universitas Pendidikan Ganesha, 2022)
Creative thinking is one of the 21st-century skills that every individual must master. Each individual has a different level of creative thinking skills. Measurement of creative thinking skills needs to be done to find out the description of students' creative thinking skills so that teachers can design methods, strategies, and learning models that can improve creative thinking skills. The purpose of this study was to analyze and describe the creative thinking skills of students. This type of research is descriptive research. The population in the study were all students of class XI. The research sample was 58 students determined using a simple random sampling technique. The instrument used is a validated questionnaire. The data collection technique is distributing questionnaires to students—data analysis in the form of descriptive analysis. The results showed that the acquisition of creative thinking skills percentage of T1 (very low) was 44.8%, T2 (low) was 35.4%, T3 (moderate) was 10.7%, T4 (high) was 5.6 %, and T5 (very high) which is 3.4%. Based on these results, it can be concluded that students' creative thinking skills are still relatively low.